Structural Transformations and Trajectory of Developing Russian Consulting - S. B. Baurina (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
Even the most successful business could come across such obstacles that would put the company out of operation. Executives and owners try to minimize costs and risks during crisis and search for support on the part of independent experts. And it is specialists on consulting, who can help disperse resources, fix in-company processes, optimize costs and provide answers to other important questions. Home literature shows academic interest in changes and transformations in Russian consulting. However, today prospects and trends of the consulting market development are rather acute, as well as integration of the Russian Federation in international consulting service market based on the new structure of international relations. These circumstances demonstrate the necessity of further academic research in this subject field and make research problems even more topical. The goal of the article is to analyze principle structural transformations and identify promising trajectories of developing Russian consulting market in conditions of global reformation of world economic links. The article shows transformation of the consulting field in current situation, highlights today’s changes and trends, researches the present day standing and assesses lines in the development of consulting market in Russia. The authors conducted structural analysis of offers on consulting service market in conditions of current changes in global policy and economy and identified priorities and prospects of consulting development in Russia. Current processes of restructuring Russian consulting market were systematized, indicators of today’s standing were specified, major trends of developing consulting service market in Russia were presented, echeloned structure of consulting offer on the market was described, priorities and prospects of developing consulting on the territory of Russia in conditions of global transformation of world economic links were grounded. Academic conclusions and findings of the research can be useful for management of Russian companies in choosing potential executors of consulting projects, at the same time they can be used by consulting company and other professional communities.